A new species of Farlowella (Siluriformes: Loricariidae) from the upper Bermejo River, La Plata River basin, northwestern Argentina - Teran, Guillermo Enrique (2019)
A new species of Farlowella is described from the Bermejo River basin, in Salta and Jujuy provinces, northwestern Argentina. The new species belongs to the Farlowella nattereri species group. The new species is diagnosed by the following combination of characters: marbled rostrum, five rows of lateral plates series, relatively short snout (snoutmouth length less than 50.0% of head length), complete half-moon shaped spot on caudal fin, and short predorsal distance (37.8-41.8% of standard length).